2015
DOI: 10.1371/journal.pone.0133377
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Evaluation of Cervical Stiffness Evolution during Induced Ripening Using Shear Wave Elastography, Histology and 2 Photon Excitation Microscopy: Insight from an Animal Model

Abstract: Prematurity affects 11% of the births and is the main cause of infant mortality. On the opposite case, the failure of induction of parturition in the case of delayed spontaneous birth is associated with fetal suffering. Both conditions are associated with precocious and/or delayed cervical ripening. Quantitative and objective information about the temporal evolution of the cervical ripening may provide a complementary method to identify cases at risk of preterm delivery and to assess the likelihood of successf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 68 publications
4
29
0
Order By: Relevance
“…2;31;49;50 Concordant with this, significant differences in SWS estimates between unripened and ripened tissue have been found in vivo and ex vivo in humans 4;6 and sheep. 13 While higher estimate uncertainty in the stiffer macaque cervix could mask small differences in stiffness, a more likely reason is that the misoprostol protocol we used is ineffective in the nonpregnant macaque. In contrast, the efficacy of misoprostol for cervical ripening in both pregnant and non-pregnant humans is well established, as is the efficacy of dexamethasone, the agent used in the study of pregnant ewes.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…2;31;49;50 Concordant with this, significant differences in SWS estimates between unripened and ripened tissue have been found in vivo and ex vivo in humans 4;6 and sheep. 13 While higher estimate uncertainty in the stiffer macaque cervix could mask small differences in stiffness, a more likely reason is that the misoprostol protocol we used is ineffective in the nonpregnant macaque. In contrast, the efficacy of misoprostol for cervical ripening in both pregnant and non-pregnant humans is well established, as is the efficacy of dexamethasone, the agent used in the study of pregnant ewes.…”
Section: Discussionmentioning
confidence: 98%
“…We and others have demonstrated its feasibility in humans and animal models. 4;68;13 This work represents our initial exploration of SWS estimation in the rhesus macaque model we are developing for comprehensive study of the pregnant cervix. The rhesus macaque carries several advantages with regard to homology with humans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The parameter used most commonly is shear wave speed group velocity ( c g , the propagation speed of the shear disturbance). Using c g , Peralta et al (2015a) reported an increase in cervical softness after labor induction in ewes. While compelling, mechanical and anatomical differences between sheep and humans may limit clinical applicability of the results.…”
Section: Introductionmentioning
confidence: 99%